2006
DOI: 10.1094/mpmi-19-0521
|View full text |Cite
|
Sign up to set email alerts
|

A Symbiont-Independent Endo-1,4-β-Xylanase from the Plant-Parasitic NematodeMeloidogyne incognita

Abstract: Substituted xylan polymers constitute a major part of the hemicellulose fraction of plant cell walls, especially in monocotyledons. Endo-1,4-β-xylanases (EC 3.2.1.8) are capable of hydrolyzing substituted xylan polymers into fragments of random size. Many herbivorous animals have evolved intimate relationships with endosymbionts to exploit their enzyme complexes for the degradation of xylan. Here, we report the first finding of a functional endo-1,4-β-xylanase gene from an animal. The gene (Mi-xyl1) was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 54 publications
4
44
0
2
Order By: Relevance
“…With respect to the well-characterized, GH family 5 endoxylanase [4,5,11,13], several authors have previously noted this classification anomaly [7,[9][10][11]. The findings presented in this work support a reclassification of these GH family 5 enzyme groups as GH30 enzymes.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…With respect to the well-characterized, GH family 5 endoxylanase [4,5,11,13], several authors have previously noted this classification anomaly [7,[9][10][11]. The findings presented in this work support a reclassification of these GH family 5 enzyme groups as GH30 enzymes.…”
Section: Discussionsupporting
confidence: 73%
“…The Carbohydrate-Active EnZymes database (CAZy) (http://www.cazy.org) [1][2][3] is the primary resource for sequence based categorization of enzymes that catalyze reactions involving the cleavage, creation or modification of glycosidic bonds. Recent biochemical characterization [4,5] and structural studies of the GH5 xylanase XynC from Bacillus subtilis [6] has directed attention to a previously noted inconsistency in the GH classification of this enzyme [7][8][9][10][11]. Early classification discussed the difficulty of making an unambiguous assignment based on hydrophobic cluster analysis comparisons with the XynC homolog, XynA from Erwinia chrysanthemi with GH family 5 and 30 (b/a) 8 barrel domains [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Jaubert et al (2005) reported a molecule Mi-CRT, localized at the tip of the nematode stylet, and at the cell wall of the GCs, supporting oesophageal molecule insertion during the establishment of NFS. Similar studies identified different candidate molecules from oesophageal gland of M. incognita (Huang et al 2005;Mitreva-Dautova et al 2006;Schaff et al 2007). Authors speculated that those molecules could be acting as a facilitator of entering and intercellular movement of the RKN at the early phases of the parasitism.…”
Section: Molecular Mechanism Of Establishing Nematode-induced Feedingmentioning
confidence: 82%
“…Comparative genomics of plant and free-living nematodes provide the essential information within the phylum Nematoda (Mitreva-Dautova et al 2006). The information from the phylum Nematoda enables us exploring the variability of parasitism genes in the field populations.…”
Section: Comparative Genomics Facilitate the Resistancementioning
confidence: 99%
“…However, the first evidence to show the animal origin of the xylanase gene, belonging to the family of GHF10, was reported in the freshwater snail A. crossean (Wang et al 2003), and later in the gastropod Pomacea canaliculata (Imjongjirak et al 2008). Xylanase, belonging to the family of GHF5, was reported in the plant-parasitic nematode Meloidogyne incognita (Mitreva-Dautova et al 2006). These findings suggest that xylanase is evolutionarily conserved and that C. japonica is possibly equipped with xylanase to effectively digest cellulose fibers in their digestive organs.…”
Section: -4 Xylanase From Corbicula Japonicamentioning
confidence: 99%